Pola Interaksi Interkomunal Umat Beragama di Kota Banda Aceh - Muhammad Sahlan (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2014)
Abstract: Intercommunity interaction among religious believer happened in two forms,  one is on daily basis and another is associational. Daily interaction is significant,  although it does not guarantee the creation of religious harmony among believers of  various religions. Meanwhile associational interaction has a role in preventing  religious conflict. However, intercommunity interaction in Banda Aceh city happens  mainly in daily basis interaction compare to associational. The imbalance in interaction  pattern will result in communication between religious believer on civil society and  elite level hindered. The implication of this is supporters or superstructure of peace and  religious harmony in Banda Aceh is fragile.  Abstrak: Interaksi interkomunal umat beragama terjadi dalam dua bentuk, yaitu  keseharian dan asosiasional. Interaksi keseharian penting, namun tidak menjamin  terciptanya kerukunan antar umat beragama. Sementara interaksi asosiasinal berperan  dalam mencegah terjadinya konflik keagamaan. Interaksi interkomunal antar umat  beragama di Kota Banda Aceh lebih sering terjadi dalam bentuk keseharian dibanding  asosiasional. Ketimpangan pola interaksi seperti ini menyebab komunikasi antar umat  beragama di tingkat menengah (civil society) dan atas (elite) tidak berjalan dengan baik.  Akibatnya basis pendukung atau suprastruktur perdamaian dan keharmonisan beragama  di Kota Banda Aceh menjadi rapuh